KUALITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) PADA BADAN PELAYANAN PERIZINAN TERPADU (BPPT) KOTA BANDUNG - Irvan Arif Kurniawan (UNIVERSITAS ISLAM SYEKH YUSUF, 2019)
The Bandung City Integrated Licensing Service Agency (BPPT) is an institution that provides one-stop licensing services, especially building construction permit (IMB) services in Bandung City. IMB services at BPPT City Bandung are carried out in an integrated manner by involving related agencies. IMB services in the city of Bandung are the services most proposed by the public. Therefore, in its implementation, it is necessary to pay attention to the quality of service. The quality of public services can be seen from the five dimensions of SERVQUAL (Service Quality), namely the tangible dimension, the reliability dimension, the responsiveness dimension, the assurance dimension, and the empathy dimension. The descriptive method was chosen to analyze the quality of IMB services at BPPT Bandung City from the five dimensions of SERVQUAL. The results of this study indicate that the tangible dimensions, dimension reliability, dimensional responsiveness, dimensional assurance, and empathy dimensions have been implemented in IMB services. Of the five dimensions, it is necessary to support adequate information technology so that building services can improve the quality of public services, especially in the dimension of responsiveness.Keyword : Service Quality, Building permit, Tangible, Reliability, Responsiveness, Assurance, and, Empahty.